2005
DOI: 10.4025/actasciagron.v27i4.1342
|View full text |Cite
|
Sign up to set email alerts
|

Produção de batata-doce e teor de amido nas raízes em função de doses de P<sub>2</sub>O<sub>5</sub>

Abstract: RESUMO.Com o objetivo de avaliar a influência da adubação fosfatada sobre a produção e sobre o teor de amido na batata-doce, cv. Rainha Branca, conduziu-se um experimento no período de fevereiro a julho/2003 em um Neossolo Regolítico Psamítico típico, textura areiafranca, na Universidade Federal da Paraíba, em Areia, Estado da Paraíba. O delineamento experimental empregado foi o de blocos casualizados com cinco tratamentos, correspondendo às doses de P 2 O 5 (0, 100, 200, 300 e 400 kg ha -1 ), em quatro repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 4 publications
0
10
1
3
Order By: Relevance
“…Furthermore, there are also some indications that P interferes with synthesis and deposition of starch in some cultures (Rosen, Kelling, Stark, & Porter, 2014;Zhao et al, 2015;A. P. Oliveira, Silva, Pereira, & Barbosa, 2005); however, this behaviour was not observed in this study.…”
Section: Figurecontrasting
confidence: 79%
“…Furthermore, there are also some indications that P interferes with synthesis and deposition of starch in some cultures (Rosen, Kelling, Stark, & Porter, 2014;Zhao et al, 2015;A. P. Oliveira, Silva, Pereira, & Barbosa, 2005); however, this behaviour was not observed in this study.…”
Section: Figurecontrasting
confidence: 79%
“…Essa diferença é explicada pelos 90 dias em que esse cultivar permaneceu no campo, além dos 180 dias do seu ciclo. Esse período a mais ocasionou no consumo do amido pela própria planta, resultando no baixo valor encontrado experimentalmente, pois as condições de umidade, temperatura, precipitação e adubação, além do tempo em que a batata-doce permanece no campo, são fatores que alteram a porcentagem de amido nas mesmas (CEREDA; VILPOUX, 2001;OLIVEIRA et al, 2005).…”
Section: Resultados E Discussõesunclassified
“…Positive results from phosphated soil fertilization on sweet potato performance are found in the literature. Oliveira et al (2005b) in studies conducted in Areia-PB evaluating the phosphorus fertilization ranging from 0 to 400 kg ha -1 P 2 O 5 , reported that total (23.5 t ha -1 ) and commercial (18.9 t ha -1 ) production of sweet potato were reached with P 2 O 5 doses 259 and 231kg ha -1 , respectively. Hameda et al (2011) found significant increases in the total sweet potatoe yield from 13.8 t ha -1 , at 15 kg ha -1 of P 2 O 5 to 16.14 t ha -1 when the P 2 O 5 dose was 45 t kg ha -1 , i.e.…”
Section: Introductionmentioning
confidence: 99%